Public-Private Partnerships in Urban Regeneration Projects: The Brazilian Context and the Case of “Porto Maravilha” in Rio de Janeiro - Paula Vale de Paula; Rui Cunha Marques; Jorge Manuel Gonçalves (Land)
Urban regeneration projects have been part of urban planning in different cities to recover strategic areas and combat new land consumption. Often, Public-Private Partnerships (PPPs) agreements are signed to meet the demands of these projects. In the Brazilian context, the general PPP law classifies concessions into two types: sponsored concessions or administrative concessions. Urban regeneration projects in the Brazilian context can be carried out through different policies and instruments, such as those in the City Statute. Despite this, there are several obstacles in how these practices are developed, which require greater attention to the enabling environment and the Critical Success Factors (CSFs) that can improve the performance of these public procurement practices. Based on this, this study aims to analyze the Brazilian context of PPP arrangements in urban regeneration projects and the specific case of the “Porto Maravilha” in Rio de Janeiro. To this scope, the study adopts a previously established CSF framework. The data analyzed are derived from secondary sources obtained through documentation collection and primary sources obtained through interviews. Regarding the PPP process, the results indicate financial and execution problems. Concerning the project, which remains unfinished, the results point to a transformation of the port area, but with significant social impacts.